Ród Gryfów (Gryfitów), rycerscy potomkowie książąt pomorskich : studium historycznoprawne - Kruszewski, Tomasz (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The author in this work develops the threads started by the late Krzysztof Mosingiewicz and Marek L. Wójcik. He holds however a radically different scientific position in comparison to the fore-mentioned authors, because those completely neglect the possibility of common descend of two families of Gryf: from Pomerania and Lesser Poland. The work has a historical-law character, because only such a form of describing this field of knowledge is possible to work out by one researcher. Genealogical studies of such an immense material are unfeasible. The Author concentrated on an analysis of participation of members of Gryf Family in holding the government and self - government office. He describes also - on a basis of remaining references – their participation in legal transactions and moreover different trains of personal law, mainly marriage and inheritance law. He analyses also various aspects between law and customs, as e.g. sexual scandal in Turscy family. The work is summed up by the assertions about offices held by members of Gryf family and question of marriage issues, in particular issues of dowry.
Keywords: Middle Ages; Pomerania; Lesser Poland; Family of Gryf; offices; marriage contract; dowry; scandals; the nobility; fortune